292 DEVELOPMENT OF A LUPUS ANTI-DNA ANTIBODY AS AN INTRACELLULAR DELIVERY VEHICLE FOR PROTEIN TRANSDUCTION OF MICRO-DYSTROPHIN. (1st January 2005) - Weisbart, R. H.; Chan, G.; Wakelin, R.
Abstract : Purpose: To produce the Fv fragment of a lupus anti-DNA autoantibody that selectively targets and penetrates skeletal muscle in vivo as a fusion protein with a micro-dystrophin for use as a non-viral delivery vehicle to transport micro-dystrophin into muscle cells. Methods: Fv-micro-dystrophin was produced as a secreted protein by transient transfection of Fv-micro-dystrophin cDNA in COS-7 cells and as a non-secreted protein by permanent transfection in Pichia pastoris. Results: Isolated Fv-micro-dystrophin was shown to be full-length by Western blot analysis. Fv-micro-dystrophin penetrated multiple cell lines in vitro and localized to the plasma membrane of a cell line with membrane beta-dystroglycan. In the absence of membrane beta-dystroglycan, it localized to the cytoplasm. Conclusion: Antibody-mediated transduction of micro-dystrophin into muscle cells is a potential therapy for dystrophin-deficient muscular dystrophies.